Composite material for anti-skid tire and preparation method thereof

By adding modified white carbon black to the tire tread rubber, the water film is pierced with its hydrophilic properties, the problem of insufficient grasping force on the slippery road surface is solved, and the anti-slip performance and driving safety are significantly improved.

CN119060429BActive Publication Date: 2025-02-28QINGDAO FULUN TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410758343.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-28
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing tire tread rubber does not hold enough under slippery road conditions, resulting in reduced driving safety.

Method used

By adding modified white carbon black to the tread rubber formula, the hydrophilic properties of the white carbon black surface are used to puncture the water film and improve the rolling resistance of the tire in wet friction.

Benefits of technology

It significantly improves the anti-slip performance of the tire, improves the grasping force of the tread glue, and improves the safety when driving on slippery roads.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a composite material for anti-skid tire and a preparation method thereof, belonging to the technical field of rubber materials. The composite material comprises the following raw materials in parts by weight: 80-120 parts of styrene-butadiene mortar, 30-50 parts of modified white carbon black, 10-20 parts of carbon black and 500-600 parts of solvent; the preparation method is as follows: adding styrene-butadiene mortar and solvent into a stirring kettle, stirring at a uniform speed for 60-80 minutes, then adding modified white carbon black and carbon black, heating to 50-65°C, continuing stirring for 2-3 hours, and then performing wet deashing, drying and briquetting to obtain the composite material for anti-skid tire; taking styrene-butadiene mortar as a matrix, introducing a large number of hydrophilic groups such as silicon oxygen bonds on the surface of white carbon black, having strong hydrophilicity, so that the white carbon black can puncture the extruded water film of the ground contact part of the tire tread, reduce the thickness of the extruded water film area, improve the rolling resistance of the tire in wet friction, and significantly improve the anti-skid property of the tread rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber materials, and in particular to a composite material for an anti-skid tire and a preparation method thereof. Background Art

[0002] Wet-skid resistance is a key indicator to measure the driving safety of automobiles, especially on slippery roads. With the development of automobile power technology and modern highways, the driving speed of automobiles has been greatly improved compared with the past, so the wet-skid resistance of tires has become more important. From the perspective of rubber viscoelasticity, the anti-wet skid performance of tread rubber can be characterized by the tan δ value at 0℃ in the dynamic viscoelastic spectrum. A high tanδ value at 0℃ indicates that the rubber has good anti-wet skid performance. However, the anti-wet skid performance of the tread material cannot be accurately determined by the viscoelasticity of the rubber, that is, the high or low tanδ value at 0℃. When the tread rubber contacts the road surface, the friction force is only affected by several to dozens of rubber molecular layers on the surface. Usually on dry roads, the traction of the tire is generated by the friction between the tread rubber and the road surface. However, when a car is driving on a wet road in rainy days, due to the presence of water, there is a layer of water film between the tire tread and the road surface, which greatly reduces the grip of the tire. If a component that can puncture the water film can be added to the tread rubber formula, the anti-wet skid performance of the tire will be significantly improved.

[0003] Trans-butadiene is a type of rubber with an allyl double bond. Due to the special structure, it has good wear resistance and oil resistance. The allyl group in trans-butadiene can react with the functional group on the surface of white carbon black through covalent bonds to form chemical bonds. The existence of this chemical bond makes the combination of trans-butadiene and carbon black more solid, which can significantly improve the wear resistance and oil resistance of rubber products. At the same time, the covalent bond reaction between trans-butadiene and white carbon black can also improve the dispersibility of carbon black in the rubber system, further improving the performance of rubber products.

[0004] There are also some problems with the addition of white carbon black and the combination with trans-butadiene. Studies have shown that the covalent bond reaction between trans-butadiene and carbon black will have a certain impact on the processing properties of rubber and easily lead to thermal aging of rubber. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a composite material for an anti-skid tire and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A composite material for anti-skid tires, comprising the following raw materials in parts by weight: 80-120 parts of styrene-butadiene rubber, 30-50 parts of modified white carbon black, 10-20 parts of carbon black, and 500-600 parts of solvent;

[0008] The modified white carbon black comprises the following steps:

[0009] Step S1, adding white carbon black to a 10% ethanol aqueous solution by volume, stirring at a uniform speed and adding KH550, heating to 40-45° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified white carbon black, and controlling the weight ratio of white carbon black to KH550 to be 10:1-2;

[0010] In step S1, the surface of silica is modified by using a silane coupling agent KH550, and amino groups are connected to the surface of silica;

[0011] Step S2, adding maleic anhydride to N,N-dimethylformamide, stirring at a uniform speed and adding 4-aminodiphenylamine, continuing stirring and reacting for 2 hours to obtain an intermediate, then adding trans-butadiene, stirring at a uniform speed and heating to 55-70° C., adding azobisisobutyronitrile, continuing stirring and reacting for 4 hours, and obtaining a prepolymer after the reaction is completed, wherein the molar ratio of maleic anhydride, 4-aminodiphenylamine and trans-butadiene is controlled to be 0.1-0.2 mol: 0.1-0.2 mol: 0.2-0.3 mol, and the amount of azobisisobutyronitrile is 3-5% of the weight of trans-butadiene;

[0012] In step S2, maleic anhydride reacts with the amino group on 4-aminodiphenylamine to prepare an intermediate, which contains a diphenylamine structure, a carboxyl group and a carbon-carbon double bond. Then, under the action of an initiator azobisisobutyronitrile, the carbon-carbon double bond on the intermediate polymerizes with trans-butadiene to prepare a prepolymer. The introduction of the trans-butadiene structure can improve the wear resistance of the tire material, and the introduced diphenylamine structure can improve the heat aging resistance of the composite material, thereby solving the problem that the introduction of trans-butadiene easily causes heat aging of the rubber.

[0013] Step S3, adding the prepared prepolymer and modified silica to N,N-dimethylformamide, heating to 55-65°C, adding concentrated sulfuric acid, stirring at a uniform speed and reacting for 6 hours, and obtaining modified silica after the reaction, controlling the weight ratio of the prepolymer to the modified silica to be 1:5-10, and controlling the weight ratio of the prepolymer to the modified silica to be 1:5-10.

[0014] In step S3, the carboxyl group on the prepolymer reacts with the amino group on the modified silica, and then the prepolymer is connected to the surface of the silica to obtain the modified silica.

[0015] Furthermore, the solvent is a mixture of one or more of cyclohexane, carbon disulfide, petroleum ether and tetrachloroethane in any proportion.

[0016] A method for preparing a composite material for an anti-skid tire comprises the following steps:

[0017] Add styrene-butadiene rubber and solvent into a stirring kettle, stir at a uniform speed for 60-80 minutes, then add modified silica and carbon black, raise the temperature to 50-65°C, continue stirring for 2-3 hours, and then undergo wet deashing, drying, and briquetting to obtain a composite material for anti-skid tires.

[0018] The beneficial effects of the present invention are as follows: the present invention prepares a composite material for tires, which uses styrene-butadiene rubber as a matrix, and has strong hydrophilicity by introducing a large number of hydrophilic groups such as silicon-oxygen bonds on the surface of white carbon black, so that the white carbon black can puncture the extruded water film of the ground contact part of the tire tread, reduce the thickness of the extruded water film area, improve the rolling resistance of the tire in wet friction, and significantly improve the anti-slip property of the tread rubber. In addition, the present invention prepares an intermediate by reacting maleic anhydride with the amino group on 4-aminodiphenylamine, and the intermediate contains a diphenylamine structure, a carboxyl group and a carbon-carbon double bond. Then, under the action of an initiator azobisisobutyronitrile, the carbon-carbon double bond on the intermediate is polymerized with trans-butadiene to prepare a prepolymer, and finally the prepolymer is grafted on the surface of white carbon black. The wear resistance of the tire material can be improved by introducing the trans-butadiene structure, and the introduced diphenylamine structure can improve the heat aging resistance of the composite material, thereby solving the problem that the introduction of trans-butadiene easily causes heat aging of the rubber. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0020] A composite material for anti-skid tires, comprising the following raw materials in parts by weight: 80 parts of styrene-butadiene rubber (SSBR2564s, solid content 10%, Dushanzi Petrochemical Company), 30 parts of modified white carbon black, 10 parts of carbon black, and 500 parts of cyclohexane;

[0021] The modified white carbon black comprises the following steps:

[0022] Step S1, adding white carbon black to a 10% ethanol aqueous solution by volume, stirring at a uniform speed and adding KH550, heating to 40° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified white carbon black, and controlling the weight ratio of white carbon black to KH550 to be 10:1;

[0023] Step S2, adding maleic anhydride to N,N-dimethylformamide, stirring at a uniform speed and adding 4-aminodiphenylamine, continuing stirring and reacting for 2 hours to obtain an intermediate, then adding trans-butadiene, stirring at a uniform speed and heating to 55° C., adding azobisisobutyronitrile, continuing stirring and reacting for 4 hours, and obtaining a prepolymer after the reaction is completed, wherein the molar ratio of maleic anhydride, 4-aminodiphenylamine and trans-butadiene is controlled to be 0.1 mol: 0.1 mol: 0.2 mol, and the amount of azobisisobutyronitrile is 3% of the weight of trans-butadiene;

[0024] Step S3, adding the prepared prepolymer and modified silica to N,N-dimethylformamide, heating to 55°C, adding concentrated sulfuric acid, stirring at a uniform speed and reacting for 6 hours, and obtaining modified silica after the reaction, controlling the weight ratio of the prepolymer to the modified silica to be 1:5, and controlling the weight ratio of the prepolymer to the modified silica to be 1:5.

[0025] A method for preparing a composite material for an anti-skid tire comprises the following steps:

[0026] Add styrene-butadiene rubber and cyclohexane into a stirring kettle, stir at a uniform speed for 60-80 minutes, then add modified silica and carbon black, raise the temperature to 50°C, continue stirring for 2 hours, and then undergo wet deashing, drying, and briquetting to obtain a composite material for anti-skid tires. Example 2

[0027] A composite material for anti-skid tires, comprising the following raw materials in parts by weight: 100 parts of styrene-butadiene rubber (SSBR2564s, solid content 10%, Dushanzi Petrochemical Company), 35 parts of modified white carbon black, 15 parts of carbon black, and 550 parts of carbon disulfide;

[0028] The modified white carbon black comprises the following steps:

[0029] Step S1, adding white carbon black to a 10% ethanol aqueous solution by volume, stirring at a uniform speed and adding KH550, heating to 42° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified white carbon black, and controlling the weight ratio of white carbon black to KH550 to be 10:1.5;

[0030] Step S2, adding maleic anhydride to N,N-dimethylformamide, stirring at a uniform speed and adding 4-aminodiphenylamine, continuing stirring and reacting for 2 hours to obtain an intermediate, then adding trans-butadiene, stirring at a uniform speed and heating to 60° C., adding azobisisobutyronitrile, continuing stirring and reacting for 4 hours, and obtaining a prepolymer after the reaction is completed, wherein the molar ratio of maleic anhydride, 4-aminodiphenylamine and trans-butadiene is controlled to be 0.12 mol: 0.12 mol: 0.25 mol, and the amount of azobisisobutyronitrile is 4% of the weight of trans-butadiene;

[0031] Step S3, adding the prepared prepolymer and modified silica to N,N-dimethylformamide, heating to 58°C, adding concentrated sulfuric acid, stirring at a uniform speed and reacting for 6 hours, and obtaining modified silica after the reaction, controlling the weight ratio of the prepolymer to the modified silica to be 1:8, and controlling the weight ratio of the prepolymer to the modified silica to be 1:6.

[0032] A method for preparing a composite material for an anti-skid tire comprises the following steps:

[0033] Add styrene-butadiene rubber and carbon disulfide into a stirring kettle, stir at a constant speed for 70 minutes, then add modified silica and carbon black, raise the temperature to 55°C, continue stirring for 2 hours, and then undergo wet deashing, drying, and briquetting to obtain a composite material for anti-skid tires. Example 3

[0034] A composite material for anti-skid tires, comprising the following raw materials in parts by weight: 110 parts of styrene-butadiene rubber (SSBR2564s, solid content 10%, Dushanzi Petrochemical Company), 45 parts of modified white carbon black, 18 parts of carbon black, and 580 parts of petroleum ether;

[0035] The modified white carbon black comprises the following steps:

[0036] Step S1, adding white carbon black to a 10% ethanol aqueous solution by volume, stirring at a uniform speed and adding KH550, heating to 45° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified white carbon black, and controlling the weight ratio of white carbon black to KH550 to be 10:2;

[0037] Step S2, adding maleic anhydride to N,N-dimethylformamide, stirring at a uniform speed and adding 4-aminodiphenylamine, continuing stirring and reacting for 2 hours to obtain an intermediate, then adding trans-butadiene, stirring at a uniform speed and heating to 70° C., adding azobisisobutyronitrile, continuing stirring and reacting for 4 hours, and obtaining a prepolymer after the reaction is completed, wherein the molar ratio of maleic anhydride, 4-aminodiphenylamine and trans-butadiene is controlled to be 0.2 mol: 0.2 mol: 0.3 mol, and the amount of azobisisobutyronitrile is 5% of the weight of trans-butadiene;

[0038] Step S3, adding the prepared prepolymer and modified silica to N,N-dimethylformamide, heating to 65°C, adding concentrated sulfuric acid, stirring at a uniform speed and reacting for 6 hours, and obtaining modified silica after the reaction, controlling the weight ratio of the prepolymer to the modified silica to be 1:10, and controlling the weight ratio of the prepolymer to the modified silica to be 1:10.

[0039] A method for preparing a composite material for an anti-skid tire comprises the following steps:

[0040] Add styrene-butadiene rubber and petroleum ether into a stirring kettle, stir at a constant speed for 80 minutes, then add modified silica and carbon black, raise the temperature to 65°C, continue stirring for 3 hours, and then undergo wet deashing, drying, and briquetting to obtain a composite material for anti-skid tires. Example 4

[0041] A composite material for anti-skid tires, comprising the following raw materials in parts by weight: 120 parts of styrene-butadiene rubber (SSBR2564s, solid content 10%, Dushanzi Petrochemical Company), 50 parts of modified white carbon black, 20 parts of carbon black, and 600 parts of tetrachloroethane;

[0042] The modified white carbon black comprises the following steps:

[0043] Step S1, adding white carbon black to a 10% ethanol aqueous solution by volume, stirring at a uniform speed and adding KH550, heating to 45° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction to obtain modified white carbon black, and controlling the weight ratio of white carbon black to KH550 to be 10:2;

[0044] Step S2, adding maleic anhydride to N,N-dimethylformamide, stirring at a uniform speed and adding 4-aminodiphenylamine, continuing stirring and reacting for 2 hours to obtain an intermediate, then adding trans-butadiene, stirring at a uniform speed and heating to 70° C., adding azobisisobutyronitrile, continuing stirring and reacting for 4 hours, and obtaining a prepolymer after the reaction is completed, wherein the molar ratio of maleic anhydride, 4-aminodiphenylamine and trans-butadiene is controlled to be 0.2 mol: 0.2 mol: 0.3 mol, and the amount of azobisisobutyronitrile is 3-5% of the weight of trans-butadiene;

[0045] Step S3, adding the prepared prepolymer and modified silica to N,N-dimethylformamide, heating to 65°C, adding concentrated sulfuric acid, stirring at a uniform speed and reacting for 6 hours, and obtaining modified silica after the reaction, controlling the weight ratio of the prepolymer to the modified silica to be 1:10, and controlling the weight ratio of the prepolymer to the modified silica to be 1:10.

[0046] A method for preparing a composite material for an anti-skid tire comprises the following steps:

[0047] Add styrene-butadiene rubber and tetrachloroethane into a stirring kettle, stir at a constant speed for 80 minutes, then add modified silica and carbon black, raise the temperature to 65°C, continue stirring for 3 hours, and then undergo wet deashing, drying, and briquetting to obtain a composite material for anti-skid tires.

[0048] Comparative Example 1

[0049] Compared with Example 4, this comparative example uses commercially available white carbon black instead of modified white carbon black.

[0050] Comparative Example 2

[0051] This comparative example does not include a styrene-butadiene rubber tire material produced by a certain company on the market.

[0052] The performance of the tire materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested, and the results are shown in Table 1 below, wherein the anti-wet skid performance of the surface material was characterized by using a BPST wet friction coefficient tester, and a high BPST anti-wet skid index indicates that the tread material has good anti-wet skid performance; the rolling resistance was characterized by the tanδ value at 60°C, and a low tanδ value at 60°C indicates that the material has low rolling resistance; the wear performance was characterized by the Akron wear volume wear amount, and a larger wear amount indicates a worse wear resistance.

[0053] Table 1

[0054] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Tensile strength MPa 26.3 26.5 26.5 26.4 23.6 16.8 Elongation at break % 572 581 580 582 526 451 Bpst anti-slip index 36 36 38 38 32 26 Tanδ0℃ 0.782 0.785 0.784 0.785 0.689 0.612 Tanδ60℃ 0.112 0.112 0.113 0.114 0.152 0.172 <![CDATA[Akhron abrasion cm 3 / 1.61 km]]> 0.156 0.158 0.157 0.158 0.192 0.281

[0055] It can be seen from Table 1 above that the tire materials prepared in Examples 1-4 of the present invention have excellent mechanical properties, as well as excellent anti-wet skid performance and wear resistance.

[0056] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A composite material for anti-skid tires, characterized in that: The invention comprises the following raw materials in parts by weight: 80-120 parts of styrene-butadiene rubber, 30-50 parts of modified white carbon black, 10-20 parts of carbon black, and 500-600 parts of solvent; The modified white carbon black comprises the following steps: Step S1, adding white carbon black to a 10% ethanol aqueous solution by volume, stirring at a uniform speed and adding KH550, heating to 40-45° C., stirring at a uniform speed and reacting for 4 hours, filtering and washing after the reaction is completed, to obtain modified white carbon black; Step S2, adding maleic anhydride to N,N-dimethylformamide, stirring at a uniform speed and adding 4-aminodiphenylamine, continuing stirring and reacting for 2 hours to obtain an intermediate, then adding trans-butadiene, stirring at a uniform speed and heating to 55-70° C., adding azobisisobutyronitrile, continuing stirring and reacting for 4 hours, and obtaining a prepolymer after the reaction is completed; Step S3, adding the prepared prepolymer and modified silica to N,N-dimethylformamide, heating to 55-65° C., adding concentrated sulfuric acid, stirring at a uniform speed and reacting for 6 hours, and obtaining modified silica after the reaction is completed, and controlling the weight ratio of the prepolymer to the modified silica to be 1:5-10.

2. The composite material for anti-skid tire according to claim 1, characterized in that: The solvent is a mixture of one or more of cyclohexane, carbon disulfide, petroleum ether and tetrachloroethane in any proportion.

3. The composite material for anti-skid tire according to claim 1, characterized in that: In step S1, the weight ratio of white carbon black to KH550 is controlled to be 10:1-2.

4. The composite material for anti-skid tire according to claim 1, characterized in that: In step S2, the molar ratio of maleic anhydride, 4-aminodiphenylamine and trans-butadiene is controlled to be 0.1-0.2 mol: 0.1-0.2 mol: 0.2-0.3 mol, and the amount of azobisisobutyronitrile is 3-5% of the weight of trans-butadiene.

5. The method for preparing a composite material for a wet skid-resistant tire according to claim 1, characterized in that: The steps include: Add styrene-butadiene rubber and solvent into a stirring kettle, stir at a uniform speed for 60-80 minutes, then add modified silica and carbon black, raise the temperature to 50-65°C, continue stirring for 2-3 hours, and then undergo wet deashing, drying, and briquetting to obtain a composite material for anti-skid tires.

Citation Information

Patent Citations

  • Production method of reactive rubber additive

    CN109593056A

  • Wet-skid-resistant rubber composition for environment-friendly tire, and preparation method thereof

    CN111073076A